Diabetes : chronic complications - Shaw, K. (Kenneth); Cummings, Michael H. (Chichester, West Sussex : Wiley-Blackwell, 2012)
This edition of Diabetes: Chronic Complications provides both the experienced and trainee endocrinologist with easy-to-read, up-to-date practical guidance on the management of the many complications that can result from the onset of diabetes, such as kidney failure, cardiovascular disease, retinal failure, and cerebrovascular disease. Reflecting the rapid developments currently taking place in the field, the second edition introduces a brand-new section on liver complications in diabetes, additional material on mental health complications in the section on diabetes and the brain, coverage of.
CHAPTER 13: Diabetes and the SkinCHAPTER 14: Diabetes and Cancer; Multiple Choice Questions; Answers; Index; Colour plates.
Includes bibliographical references and index.
Print version record.
Keywords: Diabetes -- Complications; Medicine; HEALTH & FITNESS -- Diseases -- Diabetes; Diabetes -- Complications; Medicine; Electronic books; Electronic books